Academic psychological capital questionnaire 12 (APCQ-12): psychometric validity and measurement invariance in a Chilean sample of high school students - Marcos Carmona-Halty; Geraldy Sepúlveda-Páez; Carla Semir-González; Karina Alarcón-Castillo; Patricio Mena-Chamorro (Frontiers in Psychology, 2023)
The present study evaluated the psychometric properties of the Academic Psychological Capital Questionnaire 12 (APCQ-12) in a sample of 2,196 Chilean high school students (51% girls) aged 12 to 17 years (mean 14.83 years). Results showed that: (1) the APCQ-12 produces adequate scores in terms of reliability, (2) the internal structure of the questionnaire obtains adequate fit indices, for a second order model, which is consistent with previous research, and (3) the APCQ-12 proved to be sex and age invariant. Overall, the APCQ-12 proved to be an adequate questionnaire for measuring academic psychological capital in Chilean high school students, producing valid and reliable scores.